Silicon dioxide-organic modified montmorillonite nanofiber membrane as well as preparation method and application thereof
The silica-organic modified montmorillonite nanofiber membrane prepared by electrospinning and in-situ crosslinking methods solves the problem of strength degradation of ceramic nanofiber membranes in extreme environments, and achieves the improvement of high mechanical properties, good thermal insulation properties and high temperature resistance.
Patent Information
- Application Number
- CN202510116424.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
AI Technical Summary
Ceramic nanofiber membranes are prone to strength degradation or structural collapse under mechanical stress, long-term high temperature exposure or drastic temperature changes, limiting their application in extreme environments.
Silica-organic modified montmorillonite (SiO2/O-MMT) nanofiber membrane was prepared by electrospinning and in-situ crosslinking. The O-MMT nanosheets were used to form a solid structure in the nanofiber membrane and crosslinked with SiO2 fibers by sonication and drying.
It improves the mechanical properties and thermal insulation properties of ceramic films, enhances tensile strength and ductility, reduces thermal conductivity, and improves mechanical stability and high temperature resistance.
Smart Images

Figure CN119877191A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory heat-insulating materials, and in particular to a silicon dioxide-organic modified montmorillonite nanofiber membrane and a preparation method and application thereof. Background Art
[0002] Fiber materials with thermal insulation and fire resistance are essential for wearable protective systems such as space suits, helmets, and shoes. In order to enhance thermal insulation and fire resistance, researchers have developed synthetic fibers with new compositions and structures, such as ceramic nanofiber membranes. Ceramic nanofiber membranes have light weight, low thermal conductivity, excellent fire resistance and corrosion resistance, etc. These properties are indispensable in thermal insulation protection under harsh conditions, and therefore have attracted the attention of more and more scientific researchers. However, ceramic nanofiber membranes are usually brittle and have weak mechanical properties. Therefore, they are prone to strength degradation or structural collapse under mechanical stress, long-term high temperature exposure, or rapid temperature changes, which limits their application in many cutting-edge fields, including personal protective clothing and electronic protection in extreme environments. Therefore, having strong mechanical properties in harsh environments while maintaining light weight, excellent thermal insulation and flame retardancy is a major challenge that ceramic nanofiber membranes have long faced.
[0003] In order to expand the application of SiO2 nanofiber membranes in actual production, it is crucial to develop new methods to enhance the mechanical properties of the membranes. Adding flexible one-dimensional fibers to the membrane structure is an effective way to enhance the toughness of the membrane material structure. The traditional preparation method has limited the substantial improvement of its thermal insulation performance, mechanical stability and mechanical properties due to the pores and gaps between flexible ceramic nanofibers and the lack of stable interface interactions between nanofibers. Therefore, there is still a lot of room for improvement in the mechanical properties and thermal insulation properties of ceramic nanofiber membranes. In addition, the complex preparation method of mechanically stable ceramic nanofiber membrane materials also limits its potential and development for large-scale industrial applications.
[0004] Therefore, there is an urgent need to develop a simple preparation method to enhance the thermal insulation, mechanical stability and mechanical properties of silica nanofiber membranes. Summary of the invention
[0005] The purpose of the present invention is to provide a silicon dioxide-organic modified montmorillonite nanofiber membrane and a preparation method and application thereof in order to overcome the deficiencies of the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a silicon dioxide-organically modified montmorillonite nanofiber membrane, comprising the following steps:
[0008] 1) mixing tetraethyl silicate, anhydrous ethanol, water and hydrochloric acid and heating them to obtain a silica spinning solution; spinning the silica spinning solution to obtain a silica nanofiber membrane;
[0009] adding organic modified montmorillonite into N,N-dimethylformamide and subjecting to ultrasonic treatment to obtain an organic modified montmorillonite solution;
[0010] 2) Immersing the silica nanofiber membrane in an organic modified montmorillonite solution and performing ultrasonic oscillation, and drying the ultrasonic product to obtain a silica-organic modified montmorillonite nanofiber membrane.
[0011] Preferably, the mass concentration of the hydrochloric acid in step 1) is 0.8-1.2%.
[0012] Preferably, in step 1), the mass ratio of tetraethyl silicate, anhydrous ethanol, water and hydrochloric acid is 18-19.5:7.5-8.5:2.3-3:1.2-1.32.
[0013] Preferably, the heating temperature in step 1) is 75-88° C., and the heating is carried out under stirring conditions at a stirring rate of 450-650 r / min.
[0014] Preferably, during the spinning process in step 1), the voltage is 18-25 kV and the moving speed of the spinning nozzle is 350-430 cm / min.
[0015] Preferably, in step 1), the mass volume ratio of the organic modified montmorillonite and N,N-dimethylformamide is 0.15 g:33-42 mL.
[0016] Preferably, the ultrasonic treatment time in step 1) is 1.5 to 2.5 hours; and the ultrasonic oscillation time in step 2) is 0.5 to 1 hour.
[0017] Preferably, the drying in step 2) is oven drying or shade drying, the oven drying temperature is 90-110° C., the oven drying time is 7-9 hours, and the shade drying time is 2.5-3.5 days.
[0018] The invention also provides a silicon dioxide-organic modified montmorillonite nanofiber membrane prepared by the preparation method.
[0019] The invention also provides the application of silicon dioxide-organic modified montmorillonite nanofiber membrane in thermal insulation and fire prevention.
[0020] The beneficial effects of the present invention include the following:
[0021] 1) The present invention prepares a silicon dioxide-organically modified montmorillonite (SiO2 / O-MMT) nanofiber membrane by an electrospinning method and an in-situ crosslinking method. The nanofiber membrane obtained by the electrospinning method has a uniform appearance and a large number of nanofiber gaps, which can provide a better attachment space for O-MMT. The ultra-thin O-MMT nanosheets are distributed in the nanoporous SiO2 fiber matrix and further contact the fibers. O-MMT forms a solid structure in the porous matrix and crosslinks with the SiO2 fibers. The synergistic effect improves the mechanical properties of the ceramic membrane and enhances the thermal insulation performance of the ceramic fiber membrane. In addition, the SiO2 nanofiber membrane itself is flame retardant and can better preserve its own morphology when used in thermal insulation materials.
[0022] 2) The preparation method of the SiO2 / O-MMT nanofiber membrane of the present invention is simple, and can be used to prepare fiber membranes of several times the area. It has low cost and is extremely simple to operate. It can prepare SiO2 / O-MMT nanofiber membranes with excellent ductility on a large area for thermal insulation and fire prevention. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a scanning electron microscope image of the SiO2 / O-MMT nanofiber membrane of Example 1;
[0024] Figure 2 The SiO2 / O-MMT nanofiber membrane obtained by natural shade drying in Example 2;
[0025] Figure 3 This is the morphology of the SiO2 / O-MMT nanofiber membrane of Example 1 before stretching;
[0026] Figure 4 This is the morphology of the SiO2 / O-MMT nanofiber membrane after stretching in Example 1;
[0027] Figure 5 It is a diagram of the alcohol lamp heating of the SiO2 / O-MMT nanofiber membrane of Example 1, wherein a is the nanofiber membrane heated by the alcohol lamp flame, b is the nanofiber membrane after heating, and c is the expanded diagram of the nanofiber membrane after heating;
[0028] Figure 6 This is a picture of the SiO2 / O-MMT nanofiber membrane of Example 1 immersed in liquid nitrogen. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a silicon dioxide-organically modified montmorillonite nanofiber membrane, comprising the following steps:
[0030] 1) mixing tetraethyl silicate, anhydrous ethanol, water and hydrochloric acid and heating them to obtain a silica spinning solution; spinning the silica spinning solution to obtain a silica nanofiber membrane;
[0031] The organic modified montmorillonite (O-MMT) was added into N,N-dimethylformamide and subjected to ultrasonic treatment to obtain an organic modified montmorillonite solution;
[0032] 2) Immersing the silica nanofiber membrane in an organic modified montmorillonite solution and performing ultrasonic oscillation, and drying the ultrasonic product to obtain a silica-organic modified montmorillonite (SiO2 / O-MMT) nanofiber membrane.
[0033] In the present invention, the mass concentration of the hydrochloric acid in step 1) is preferably 0.8-1.2%, more preferably 0.9-1.1%, and more preferably 1.0%.
[0034] In the present invention, the mass ratio of tetraethyl silicate, anhydrous ethanol, water and hydrochloric acid in step 1) is preferably 18-19.5:7.5-8.5:2.3-3:1.2-1.32, more preferably 18.3-19.2:7.7-8.3:2.4-2.8:1.23-1.3, and more preferably 18.5-18.8:7.9-8.0:2.5-2.6:1.26-1.28.
[0035] In the present invention, the heating temperature in step 1) is preferably 75-88°C, more preferably 78-85°C, and more preferably 80-82°C. The heating is preferably carried out under stirring conditions, and the stirring rate is preferably 450-650r / min, more preferably 480-620r / min, and more preferably 500-600r / min.
[0036] In the present invention, during the spinning process in step 1), the voltage is preferably 18-25 kV, more preferably 20-23 kV, more preferably 21-22 kV, and the moving speed of the spinning nozzle is preferably 350-430 cm / min, more preferably 370-410 cm / min, more preferably 380-400 cm / min.
[0037] In the present invention, the moving speed of the spinning nozzle is the left-right moving speed of the spinning nozzle, and the left-right moving distance of the spinning nozzle is equal to the width of the receiving plate (receiving roller).
[0038] In the present invention, the silica nanofibers are spun onto tin foil or silicone oil paper in a spindle shape to obtain a silica nanofiber membrane.
[0039] In the present invention, the mass volume ratio of the organic modified montmorillonite and N,N-dimethylformamide in step 1) is preferably 0.15g:33-42mL, more preferably 0.15g:35-40mL, and more preferably 0.15g:37-38mL.
[0040] In the present invention, the ultrasonic treatment time in step 1) is preferably 1.5 to 2.5 h, more preferably 2 h; the ultrasonic oscillation time in step 2) is preferably 0.5 to 1 h, more preferably 0.75 h.
[0041] In the present invention, the immersion in step 2) is that the silicon dioxide nanofiber membrane is completely immersed in the organic modified montmorillonite solution.
[0042] In the present invention, the drying in step 2) is preferably a baking treatment or a shade drying treatment, the baking treatment temperature is preferably 90-110°C, more preferably 95-105°C, more preferably 100°C, the baking treatment time is preferably 7-9h, more preferably 7.5-8.5h, more preferably 8h; the shade drying time is preferably 2.5-3.5d, more preferably 3d.
[0043] The invention also provides a silicon dioxide-organic modified montmorillonite nanofiber membrane prepared by the preparation method.
[0044] In the silicon dioxide / organic modified montmorillonite nanofiber membrane of the present invention, O-MMT is evenly dispersed in the fiber pores in the form of flakes.
[0045] The invention also provides the application of silicon dioxide-organic modified montmorillonite nanofiber membrane in thermal insulation and fire prevention.
[0046] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0047] In the embodiment, the organic modified montmorillonite is the DK5 model organic montmorillonite of Zhejiang Fenghong New Materials Co., Ltd.; the model of the electrospinning machine is JDF05, purchased from Changsha Nayi Instrument Technology Co., Ltd.; the power of ultrasonic treatment and ultrasonic oscillation are both 500W, and the frequency is both 40kHz.
[0048] Example 1
[0049] 18.8 g of tetraethyl silicate, 7.9 g of anhydrous ethanol, 2.6 g of pure water, and 1.26 g of hydrochloric acid with a mass concentration of 1% are mixed in order to obtain a silica nanofiber solution; the silica nanofiber solution is heated in a magnetic stirrer, the temperature is set to 80° C., and the rotation speed is set to 500 r / min to obtain a silica spinning solution.
[0050] The silica spinning solution was placed in an electrospinning machine for spinning. The voltage was set to 20 kV, the spinning nozzle moved left and right at a speed of 400 cm / min, and the silica nanofibers were spun onto the tin foil in a spindle shape to obtain a silica nanofiber membrane.
[0051] 0.15 g of O-MMT was added to 40 mL of N,N-dimethylformamide and ultrasonically treated for 2 h to obtain an O-MMT solution. A silica nanofiber membrane (size 5 cm×5 cm) was immersed in the O-MMT solution and ultrasonically shaken for 0.5 h. The ultrasonic product was dried at 100°C for 8 h to obtain a SiO2 / O-MMT nanofiber membrane.
[0052] Example 2
[0053] 18.8 g of tetraethyl silicate, 8.0 g of anhydrous ethanol, 2.6 g of pure water, and 1.28 g of hydrochloric acid with a mass concentration of 1% are mixed in order to obtain a silica nanofiber solution; the silica nanofiber solution is heated in a magnetic stirrer, the temperature is set to 82° C., and the rotation speed is set to 600 r / min to obtain a silica spinning solution.
[0054] The silica spinning solution was placed in an electrospinning machine for spinning. The voltage was set to 21 kV, the spinning nozzle moved left and right at a speed of 380 cm / min, and the silica nanofibers were spun onto the silicone oil paper in a spindle shape to obtain a silica nanofiber membrane.
[0055] 0.15 g of O-MMT was added to 35 mL of N,N-dimethylformamide and ultrasonically treated for 2 h to obtain an O-MMT solution. A silica nanofiber membrane (size 5 cm×5 cm) was immersed in the O-MMT solution and ultrasonically shaken for 0.5 h. The ultrasonic product was naturally dried in the shade for 3 days to obtain a SiO2 / O-MMT nanofiber membrane.
[0056] Example 3
[0057] 18.5 g of tetraethyl silicate, 7.7 g of anhydrous ethanol, 2.4 g of pure water, and 1.23 g of hydrochloric acid with a mass concentration of 1.1% are mixed in order to obtain a silica nanofiber solution; the silica nanofiber solution is heated in a magnetic stirrer, the temperature is set to 78° C., and the rotation speed is set to 480 r / min to obtain a silica spinning solution.
[0058] The silica spinning solution was placed in an electrospinning machine for spinning. The voltage was set to 18 kV, the spinning nozzle moved left and right at a speed of 410 cm / min, and the silica nanofibers were spun onto the tin foil in a spindle shape to obtain a silica nanofiber membrane.
[0059] 0.15 g of O-MMT was added to 37 mL of N,N-dimethylformamide and ultrasonically treated for 2.5 h to obtain an O-MMT solution. A silica nanofiber membrane (size 5 cm × 5 cm) was immersed in the O-MMT solution and ultrasonically shaken for 1 h. The ultrasonic product was dried at 105 ° C for 7 h to obtain a SiO2 / O-MMT nanofiber membrane.
[0060] Figure 1 This is a scanning electron microscope image of the SiO2 / O-MMT nanofiber membrane of Example 1, in which the two pictures in the upper left corner show the flexibility and foldability of the nanofiber membrane. The red circle in the flexibility image is the cross-linking between the layers formed by MMT and the fibers.
[0061] Figure 2 The SiO2 / O-MMT nanofiber membrane obtained by natural shade drying in Example 2; Figure 3 This is the morphology of the SiO2 / O-MMT nanofiber membrane of Example 1 before stretching; Figure 4 This is the morphology of the SiO2 / O-MMT nanofiber membrane after stretching in Example 1.
[0062] The thermal insulation and mechanical properties of the SiO2 / O-MMT nanofiber membranes prepared in Examples 1 to 3 were tested.
[0063] Thermal insulation performance test: The thermal constant analyzer Hot Disk TPS2500S was used for testing. The thermal conductivity of the SiO2 / O-MMT nanofiber membranes in Examples 1 to 3 was 0.037 W·m -1 ·K -1 , 0.035W·m -1 ·K -1 , 0.038W·m -1 ·K -1 .
[0064] Mechanical properties test: Mechanical properties test was conducted using a mechanical properties tester (tensile testing machine, model ZQ-990A, Dongguan Zhiqu Precision Instrument Co., Ltd.). Compared with the silica nanofiber membrane without O-MMT, the tensile strengths of the SiO2 / O-MMT nanofiber membranes of Examples 1 to 3 were 1.25MPa, 1.23MPa, and 1.24MPa, respectively, which were 2 to 3 times higher than the tensile strength of the silica fiber membrane without montmorillonite. Ductility is the maximum length that can be stretched without breaking. The tensile length of the SiO2 / O-MMT nanofiber membrane measured by the tensile testing machine increased by 2 to 3 times; the tensile strengths of the SiO2 / O-MMT nanofiber membranes of Examples 1 to 3 were 0.53MPa, 0.51MPa, and 0.52MPa, respectively.
[0065] Figure 5 1 is a diagram of the alcohol lamp heating of the SiO2 / O-MMT nanofiber membrane of Example 1, wherein a is the nanofiber membrane heated by the outer flame of the alcohol lamp, b is the nanofiber membrane after heating, and c is the expanded diagram of the nanofiber membrane after heating; Figure 5 From b and c, it can be seen that the shape and appearance of the nanofiber membrane did not change significantly after being heated by the outer flame of an alcohol lamp (600°C). After heating, the membrane was unfolded and could be restored to its original shape without cracks. The nanofiber membrane still maintained its flexibility when heated by an alcohol lamp.
[0066] Figure 6 This is a picture of the SiO2 / O-MMT nanofiber membrane of Example 1 immersed in liquid nitrogen. It can be seen from the picture that the SiO2 / O-MMT nanofiber membrane maintains flexibility in liquid nitrogen.
[0067] The present invention prepares a SiO2 / O-MMT nanofiber membrane by cross-linking and assembling silica nanofibers and montmorillonite (O-MMT) nanosheets; the silica nanofiber membrane is immersed in an O-MMT solution, the residual liquid is removed by drying and the O-MMT is attached to the gaps in the nanofibers. The prepared SiO2 / O-MMT nanofiber membrane has high flexibility and does not break when bent. In terms of ductility, it can be stretched to a length of 2 to 3 times its own length, and the tensile strength can reach more than 1.23 MPa. It has good mechanical stability and high temperature resistance. The cross-linking effect between the SiO2 nanofibers and the O-MMT nanosheets makes the SiO2 / O-MMT nanofiber membrane have a low thermal conductivity. The SiO2 / O-MMT nanofiber membrane of the present invention is expected to become an ideal material for the manufacture of next-generation firefighter uniforms, providing a basis for their large-scale industrial production.
[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a silicon dioxide-organically modified montmorillonite nanofiber membrane, characterized in that: The following steps are included: 1) mixing tetraethyl silicate, anhydrous ethanol, water and hydrochloric acid and heating them to obtain a silica spinning solution; spinning the silica spinning solution to obtain a silica nanofiber membrane; The organic modified montmorillonite is added into N,N-dimethylformamide and subjected to ultrasonic treatment to obtain an organic modified montmorillonite solution; 2) Immersing the silica nanofiber membrane in an organic modified montmorillonite solution and performing ultrasonic oscillation, and drying the ultrasonic product to obtain a silica-organic modified montmorillonite nanofiber membrane.
2. The preparation method according to claim 1, characterized in that: The mass concentration of the hydrochloric acid in step 1) is 0.8-1.2%.
3. The preparation method according to claim 1 or 2, characterized in that: In step 1), the mass ratio of tetraethyl silicate, anhydrous ethanol, water and hydrochloric acid is 18-19.5:7.5-8.5:2.3-3:1.2-1.
32.
4. The preparation method according to claim 3, characterized in that: Step 1) The heating temperature is 75-88° C., and the heating is carried out under stirring conditions at a stirring rate of 450-650 r / min.
5. The preparation method according to claim 3, characterized in that: In step 1), during the spinning process, the voltage is 18-25 kV, and the moving speed of the spinning nozzle is 350-430 cm / min.
6. The preparation method according to claim 1, characterized in that: Step 1) The mass volume ratio of the organic modified montmorillonite and N,N-dimethylformamide is 0.15 g: 33-42 mL.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The ultrasonic treatment time in step 1) is 1.5 to 2.5 hours; the ultrasonic oscillation time in step 2) is 0.5 to 1 hour.
8. The preparation method according to claim 1, characterized in that: Step 2) The drying is oven drying or shade drying. The oven drying temperature is 90-110° C. and the oven drying time is 7-9 hours. The shade drying time is 2.5-3.5 days.
9. The silica-organically modified montmorillonite nanofiber membrane prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the silica-organically modified montmorillonite nanofiber membrane according to claim 9 in thermal insulation and fire protection.
Citation Information
Patent Citations
Preparation method of high elasticity super hydrophobic high temperature nano silicon dioxide fibrous membrane
CN101603245A
Preparation method of high temperature resistant silicon dioxide nanometer fiber filtering membrane
CN102652903A
Novel rare earth flexible thermal insulation material and preparation method thereof
CN118292260A
Flame-retardant knitted fabric and preparation method therefor
WO2023123391A1
Cited By
Wear-resistant blended gradient needling filtering material and preparation method thereof
CN121754960A